Diagnostic Value of Determination Blast Cell Population Lineage Using WPC Scattergram Hematology Analyzer - Nina Ratnasari; Arifoel Hajat; S. Ugroseno Yudho Bintoro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The diagnosis of hematology malignancies requires examination that includes morphology, immunophenotyping, and cytogenetics. Immunophenotyping is the most trusted examination in determining hematology malignancies lineage, but it is only available in large hospitals and the costs are relatively expensive, so the determination of lineage depends on bone marrow aspiration examination. Therefore it is necessary to have an easier and more reliable alternative to assist BMA morphology. White Precursor Cell (WPC) scattergram Sysmex XN-1000 has the capability to differentiate malignancy lineage. The purpose of this study was to determine the diagnostic value of determining lineage generated by WPC scattergram compared to the lineage from BMA examination. BMA blood samples were simultaneously examined by BMA morphology interpretation using microscope and WPC scattergram Sysmex XN-1000 examination. The hematology malignancies lineage resulting from BMA and WPC scattergram examination was then analyzed statistically to determine the suitability, sensitivity, and specificity. The results of determining the lineage of blast cell population based on WPC scattergram resulted in a suitability with a sensitivity of 93.75% and specificity of 94.74% for determining the hematological malignancy of myeloid lineage and 94.74% and 93.75% for lymphoid lineage, with a diagnostic accuracy of 94.91%. Based on this study it can be concluded that the WPC scattergram can determine the lineage of hematological malignancies with a suitability and high diagnostic value of lineage based on BMA morphology.